2018
DOI: 10.3390/nu10030337
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a Protein Supplement on the Gut Microbiota of Endurance Athletes: A Randomized, Controlled, Double-Blind Pilot Study

Abstract: Nutritional supplements are popular among athletes to improve performance and physical recovery. Protein supplements fulfill this function by improving performance and increasing muscle mass; however, their effect on other organs or systems is less well known. Diet alterations can induce gut microbiota imbalance, with beneficial or deleterious consequences for the host. To test this, we performed a randomized pilot study in cross-country runners whose diets were complemented with a protein supplement (whey iso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
74
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(94 citation statements)
references
References 61 publications
(69 reference statements)
3
74
0
3
Order By: Relevance
“…In a Bacteroides -dominant cooperative, a number of member genera is associated with diets rich in animal protein [ 51 ] and includes Alistipes , Bacteroides , Barnesiella, and Parabacteroides species, some of which are known to be bile-tolerant [ 43 ]. An inclusion of Oscillospira in this cooperative may be due to cross-feeding effects through the use of the fermentation by-products of Bacteroides [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…In a Bacteroides -dominant cooperative, a number of member genera is associated with diets rich in animal protein [ 51 ] and includes Alistipes , Bacteroides , Barnesiella, and Parabacteroides species, some of which are known to be bile-tolerant [ 43 ]. An inclusion of Oscillospira in this cooperative may be due to cross-feeding effects through the use of the fermentation by-products of Bacteroides [ 52 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreno-Perez et al [186] evaluated the effect of 10-week protein supplementation (10 g of whey isolate plus 10 g of beef hydrolysate protein per day) on gut microbiota in recreational endurance athletes. Although there was no effect of SCFAs, ammonia, or faecal pH, they reported a decrease in health-promoting bacteria (Roseburia, Blautia, and Bifidobacterium longum); based on these data, the authors concluded that long-term protein supplementation might harm the gut microbiota of athletes.…”
Section: Proteinsmentioning
confidence: 99%
“…Effects of protein supplementation for microbiota in athletes should be taken into consideration since nutritional recommendations regarding protein consumption in this population are higher than for the general population. The long-term consequences of the decrease in these bacterial taxa (Blautia, Roseburia, and Bifidobacterium longum) for gut health are unknown [186].…”
Section: Proteinsmentioning
confidence: 99%
“…It has been established, that the consumption of soy protein can modify the taxonomy of the gut microbiota. [18][19][20][21][22][23] In the last decade, animal and human studies have demonstrated that during obesity, there is a dysbiosis of the gut microbiota, and it has been associated with the appearance of metabolic endotoxemia, [24] glucose intolerance, and insulin resistance. [25] Thus, it could be possible that the metabolic health benefits observed during the consumption of a soy protein diet could be mediated by preventing the gut microbiota dysbiosis, even after the consumption of a high-fat diet.…”
Section: Introductionmentioning
confidence: 99%